Dendrimer-entrapped gold nanoparticles as promising nanocarriers for anticancer therapeutics and imaging. (June 2019) - Kesharwani, Prashant; Choudhury, Hira; Meher, Jaya Gopal; Pandey, Manisha; Gorain, Bapi
Abstract: Theranostic nanotherapeutic strategy has been widely emphasized now a day to develop next-generation nanomedicine. Dendrimer-entrapped gold nanoparticles (DE-Au-NP) have acquired emerging application in therapeutic, imaging as well as in theranostics sciences. DE-Au-NP decorated with a specific ligand for cancer cells could deliver contrast agents at target sites for imaging as well as chemotherapeutics for anticancer activity. Entrapped Au in DE-Au-NP complex could serve as an excellent contrast agent for CT imaging with better signal intensity to identify initial stages of cancer, whereas its photothermal effect can kill cancerous cells effectively. Although, reported nonspecific binding of DE-Au-NP due to free amine groups and associated toxicities of dendrimer complex could be minimized through PEGylation or acetylation of such surface amines. Recent research on gene delivery also revealed DE-Au-NP as an active tool to deliver plasmids to cancer cells to express/suppress particular protein(s) to combat against cancer.